Hubungan Usia Anak Penderita Thalasemia Dengan Frekuensi Transfusi - Irdawati Irdawati; Afifah Ayu Syaiful; Anis Haryani (Jurnal Berita Ilmu Keperawatan, 2021)
Introduction Thalassemia is a genetic disease that is detected when someone is still a child. as an effect of this disease the child can not be separated from the treatment of blood transfusion. Treatment of transfusion in patients with thalassemia is the only way to prevent death in children. Thalassemia children visit to do blood transfusion to the hospital an average of 2 to 3 times within a month. Thalassemia patients must undergo regular and routine blood transfusions to maintain their health and stamina, so that patients can still be active. Transfusion will provide new energy to the patient because the blood from the transfusion has a normal hemoglobin level able to meet the needs of the patient's body to live everyday life. The purpose of this study was to determine the relationship between the age of children with thalassemia with frequency of transfusion. This type of research is cross sectional. Cross sectional research is research that aims to study the relationship between factors and the effects it causes. The sample used in this study was 30 samples. The sampling technique uses accidental sampling. The research instrument used was a questionnaire sheet. The questionnaire in this study is a questionnaire made by the researcher based on operational definitions, therefore the researcher first tests the validity and reliability before the research. The research results obtained from the analysis of the relationship test results (p-value = 0.036). This p-value is smaller than the established α value of 0.05 (5%). So that Ho is rejected, the conclusion is that there is a significant relationship between the age of the child with thalassemia patients. Based on this study it was found that there is a relationship between the age of the child with the frequency of transfusion.